1995
DOI: 10.1016/0009-9236(95)90074-8
|View full text |Cite
|
Sign up to set email alerts
|

H1- and H2-histamine receptor—mediated vasodilation varies with aging in humans*

Abstract: These results suggest that, although the overall histamine-induced venodilation is conserved in aging, there is a loss of the signal transduction pathway activated by way of H2-receptors but no loss in function of H1-receptors. Consequently, these results suggest differential changes in function of H1- versus H2-histamine receptors with aging. Because H1-receptors are coupled to endothelial-derived relaxing factor release and because H2-receptors activate cyclic adenosine monophosphate in smooth muscle, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Finally, amitriptyline has affinity not only for noradrenaline uptake and el-adrenoceptors, but also for muscarinic cholinoceptors and H1 histamine receptors (Hall and CIgren 1981;Richelson and Nelson 1984). There is evidence both for venodilator muscarinic (Collier et al 1972;Kongpatanakul et al 1992) and H1 histamine receptors (Dachman et al 1994;Bedarida et al 1995) in the dorsal hand vein. Although, in theory, the blockade of these receptors by amitriptyline could have caused an increase in the size of the response to noradrenaline, the same mechanism would have increased the size of the responses to methoxamine as well.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, amitriptyline has affinity not only for noradrenaline uptake and el-adrenoceptors, but also for muscarinic cholinoceptors and H1 histamine receptors (Hall and CIgren 1981;Richelson and Nelson 1984). There is evidence both for venodilator muscarinic (Collier et al 1972;Kongpatanakul et al 1992) and H1 histamine receptors (Dachman et al 1994;Bedarida et al 1995) in the dorsal hand vein. Although, in theory, the blockade of these receptors by amitriptyline could have caused an increase in the size of the response to noradrenaline, the same mechanism would have increased the size of the responses to methoxamine as well.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine challenge in migraine patients and healthy volunteers, respectively, induced a migraine attack and headache (25–27). Histamine is a potent vasoactive compound (28–35), and since the headache of a migraine attack has been attributed to cerebrovascular vasodilation (36–39), histamine may be a candidate mediator for vascular changes observed during a migraine attack. There is evidence that the vascular effects of histamine are at least partially mediated by nitric oxide (NO) (40), a gaseous molecule with a potential important role in development of migraine.…”
Section: Methodsmentioning
confidence: 99%
“…In the human brain, similar observations were noted, where the H1 receptor subtype showed significant decreases with age 24 . The ability of histamine to induce vasodilation via the activation of H1 and H2 receptors is also altered with age 25 . The authors demonstrated that ageing has a direct effect on the signal transduction pathway activated via the H2 receptor while maintaining the function of H1 receptor.…”
mentioning
confidence: 99%